Risk Factors of Oral Cancer and Potentially malignant disorders (PMDs) – Developing a High / Low Risk Profiling System - Diajil, Ameena R; Thomson, Peter (Journal of Baghdad College of Dentistry, 2016)
Background: Oral squamous cell carcinoma (OSCC) remains a lethal and deforming disease, with a significant mortality and a rising incidence in younger and female patients. It is thus imperative to identify potential risk factors for OSCC and oral PMDs and to design an accurate data collection tool to try to identify patients at high risk of OSCC development. 14 factors consistently found to be associated with the pathogenesis of OSCC and oral PMDs. Eight of themwere identified as high risk (including tobacco, alcohol, betel quid, marijuana, genetic factors, age, diet and immunodeficiency) and 6 low risk (such as oral health, socioeconomic status, HPV, candida infection, alcoholic mouth wash and diabetes) were stratified according to severity of risk, associated carcinogenicity and clinicopathological effects, using evidence obtained from the International Agency for Research on Cancer (IARC). This review provides understanding of the significance of various risk factors in oral carcinogenesis to help to stratify patients, especially those with potentially malignant disorders, into high and low risk groups. Key words: Oral cancer, oral potentially malignant disorders and risk factor.